ANALISIS PENILAIAN KINERJA KEUANGAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) - Tri Wahyuningrum (STIE BIITM, 2019)
Anticipating the development of a thriving business world today required the professionalism of leaders and their staff in managing the company to achieve the objectives set. The purpose of this research is to analyse the financial performance of CV. Rumah Roti using the method of Economic Value Added (EVA). The analytical methods used are weighted average cost of capital analysis, NOPAT analysis and EVA analysis. Based on the cost of capital analysis, the company showed that the weighted average cost of capital over the last 5 years from 2014 to 2018 increased and decrease flutuatively which the reason was a difference Amount of loan capital annually. The amount of corporate loan capital customized to the company's needs. From the EVA analysis, the result is all positive EVA figures, nothing negative. These results indicate that the existence of the value of capital used during the year 2014 to 2018. Although like in the years 2015 and 2017 the company experienced a decline in financial value, but the EVA figures still positive which means that the company is still operating at a favorable rate when compared to its capital costs.